Dimer excision and repair replication patch size in recL152 mutant of Escherichia coli K-12. - Rothman, R H (1978)
Dimers are excised slowly in a recL152 mutant. This observation is not an artifact of altered DNA degradation because degradation is the same in recL+ and recL strains. The repair patch size was measured by the bromodeoxyuridine-313 nm radiation photolysis technique. In the recL+ strain, the average patch size was found to be about 30 nucleotides in length, but in the recL mutant, it was about 360.